2021
DOI: 10.3389/fmolb.2021.643504
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles of Circular RNAs and MicroRNAs in Chronic Rhinosinusitis With Nasal Polyps

Abstract: Introduction: Chronic rhinosinusitis (CRS) is often classified primarily on the basis of the absence or presence of nasal polyps (NPs), that is, as CRS with nasal polyps (CRSwNP) or CRS without nasal polyps (CRSsNP). Additionally, according to the percentage of eosinophils, CRSwNP can be further divided into eosinophilic CRSwNP (ECRSwNP) and non-ECRSwNP. CRSwNP is a significant public health problem with a considerable socioeconomic burden. Previous research reported that the pathophysiology of CRSwNP is a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Research by Yu et al identified the differential expression of 2875 circRNAs and 192 miRNAs between CRSwNP subjects and control subjects. 7 This indicated that circRNAs and miRNAs may play important roles in the occurrence and development of CRSwNP. However, how these circRNAs and miRNAs interact to regulate CRSwNP remained unknown.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Research by Yu et al identified the differential expression of 2875 circRNAs and 192 miRNAs between CRSwNP subjects and control subjects. 7 This indicated that circRNAs and miRNAs may play important roles in the occurrence and development of CRSwNP. However, how these circRNAs and miRNAs interact to regulate CRSwNP remained unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Hsa_circ_0031594 is upregulated in CRSwNP, which is consistent with a previous report. 7 Hsa-miR-6507-5p has been reported to be upregulated in patients with achalasia, however its mechanism has not been studied. 59 We found that hsa-miR-6507-5p and hsa-miR-1260b were downregulated in CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations